2019
DOI: 10.4049/jimmunol.1801511
|View full text |Cite
|
Sign up to set email alerts
|

NK Response Correlates with HIV Decrease in Pegylated IFN-α2a–Treated Antiretroviral Therapy–Suppressed Subjects

Abstract: We previously reported that pegylated IFN-a2a (Peg-IFN-a2a) added to antiretroviral therapy (ART)-suppressed, HIV-infected subjects resulted in plasma HIV control and integrated HIV DNA decrease. We now evaluated whether innate NK cell activity or PBMC transcriptional profiles were associated with decreases in HIV measures. Human peripheral blood was analyzed prior to Peg-IFN-a2a administration (ART, baseline), after 5 wk of ART+Peg-IFN-a2a, and after 12 wk of Peg-IFN-a2a monotherapy (primary endpoint). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 80 publications
1
16
0
1
Order By: Relevance
“…CD8 + T and NK cell functions are important for the antiviral effect of IFNα treatment [38] and the impact of IFNα on levels of integrated HIV DNA was associated with NK activation and cytotoxic response to K562 target cells [39] . To examine the links between IFNα-mediated alterations in IgG glycosylation, inflammatory markers, and immune functions, we evaluated CD8 + T cell (without stimulation) and NK cell (upon K562 stimulation) phenotypes using flow cytometry (green and blue arcs in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD8 + T and NK cell functions are important for the antiviral effect of IFNα treatment [38] and the impact of IFNα on levels of integrated HIV DNA was associated with NK activation and cytotoxic response to K562 target cells [39] . To examine the links between IFNα-mediated alterations in IgG glycosylation, inflammatory markers, and immune functions, we evaluated CD8 + T cell (without stimulation) and NK cell (upon K562 stimulation) phenotypes using flow cytometry (green and blue arcs in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our observations that IFNα induces sialic acid on the NK surface and that this induction correlates negatively with NK functions warrant further investigation. IFNα is an activator of NK cell functions [75 , 76] , and the positive impact of IFNα on levels of integrated HIV DNA was associated with NK activation and cytotoxic response to K562 target cells [39] . However, IFNα-mediated induction of sialic acid may exert a negative effect that hampers taking full advantage of the positive impact of IFNα on NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that ART cessation likely induces near-maximal IFN-I responses at the sites of virus recrudescence will need to be factored into the design of these strategies. Consistent with this, a recent study found that activation of NK cell cytotoxicity, and not the induction of interferon stimulated genes, correlated with exogenous IFNα2-mediated HIV-1 control ( 85 ).…”
Section: Discussionmentioning
confidence: 55%
“…1C). ART was initiated in eight participants between 85 and 323 weeks post onset of symptoms based on the standard-of-care at the time (shaded in Fig. 1).…”
Section: Generation Of Plasma Isolates From Longitudinally Sampled Inmentioning
confidence: 99%
“…For example, ex vivo IL-21 treatment expanded CD16 + NK cells 9 , antagonized the IL-15-dependent expansion of resting NK cells 10 , and reverses hypo-responsiveness via the STAT1 and PI3K-AKT-FOXO1 pathways 11 . Likewise, ex vivo IFNα therapy upregulates IL-15-mediated NK cell cytotoxicity 12 , including CD107a degranulation and ADCC activity 13,14 , and downregulates IL-21R expression 15 ; furthermore, in vivo IFNα-induced NK cell cytotoxicity correlates with reductions in HIV-DNA during antiretroviral therapy (ART) 16 . In SIVagm infection, systemic IL-15 was associated with NK cell proliferation in lymph node (LN), while systemic IFNα correlated with NK cell cytotoxicity in LN 17 .…”
mentioning
confidence: 99%